Data Mining Penjualan Tanaman Hias dengan Algoritma APRIORI Pada Toko Flores Elishabet - Yendrizal, Yendrizal (STMIK Budi Darma, 2020)
The application of data mining is very useful in the sale of ornamental plants and can affect the ups and downs of the sales turnover of ornamental plants, the many types of ornamental plants and types of flowers and their different names make people interested in ornamental plants confused in the search for ornamental plants to be purchased. The higher interest in purchasing ornamental plants makes the amount of data and information that needs to be known and explored efforts to find out which type of ornamental plant that has a lot of interest, usually people not only buy one type of ornamental plant, but there are also other types of ornamental plants that are also purchased. Apriori algorithm is an algorithm in data retrieval using association rules that aim to determine the associative relationship of a combination of items, data mining itself is a way of computerization in marketing strategies